(In) stability, a key element to understand participatory budgeting: Discussing Portuguese cases - Alves, Mariana Lopes (2012)
Much has been said about Participatory Budgeting. Still, how to make it a successful and long-lasting experience remains open for debate. Studies have advanced in analyzing many PB “features”, discussing its capacity to promote transparency, empowerment and accountability. However, little was said about its capacity to maintain continuity over time. With the increasing number of experiences all over the world we can observe that not always the numeric growth represent the emergency of strong and stable experiences. Many Participatory Budgeting experiences are implemented but after a short time disappear from the local political agenda. In this paper we analyze the Portuguese Participatory Budgeting panorama discussing the phenomenon of fragility and volatility that many PB have faced in this country. We argue that the explanatory power of some apparently important variables, such as ruling party change, is very limited. Finally, based on the empirical discussion we propose an analytical model that may help to understand the dynamics of this phenomenon in Portugal and other countries. We think that identifying “fragility” points is an important step for enhancing Participatory Budgeting experiences.